Pharmacokinetics And Infant Exposure of Citalopram and Demethylcitalopram in Breastfeeding Women - Kumar C, Kishore; Kesamreddy, Swetha; Rani Hasthi, Usha (Journal of Neonatal Surgery, 2025)
The project is aimed at exploring the excretion of citalopram and its first metabolite, demethylcitalopram, in breast milk in a group of 11 women with breastfeeding and their children. Citalopram is a well-known antidepressant which is used very often to cure the depression; however, there are still notions referring to transferring the drug to breast milk and the results of this impact on a child. We measured the pharmacokinetics of citalopram and demethylcitalopram in the maternal plasma, the breast milk and the infant plasma. In the study citalopram was identified to be transferred into breast milk in greater amounts than demethylcitalopram, peaking in milk at 2-8 hours following medication. Nonetheless, the estimated infant exposures to the two drugs were minimal with doses of less than 5 percent of the dose by the mother. There were no adverse effects reported in the infants and they all had normal developments as tested by Denver developmental screening test. These results indicate the fact that citalopram is, most likely, safe in a breastfeeding mother. Nevertheless, the breastfeeding during the reception of citalopram is always the question which is to be considered separately, according to the personal risks and the benefits each time.